Efforts to Improve Understanding of the Food Chain Concept Through Direct Instruction Learning Model for Elementary School Students - Joko Priyanto (Universitas Sebelas Maret, 2020)
The goal to be achieved in this research is to improve understanding of the concept of the food chain through the Direct Instruction learning model for grade V students of SD Negeri 2 Muruh in the academic year 2020/2021. This research is a classroom action research (PTK). The research was conducted in two cycles. Each cycle consists of planning, acting, observing, and reflecting. The subjects of this study were students of class V SD Negeri 2 Muruh with 16 students. Data collection techniques using documentation, observation, and tests. The data analysis technique used is a comparative descriptive model, which is to compare the value of students' understanding of the food chain concept from the initial conditions, cycle I, to cycle II. The results showed an increase in the class average score and the number of students who completed learning in each cycle. In the initial conditions, the class average score was only 67.93 with the number of students who completed as many as 8 students or 50%. The class average score in the first cycle increased to 71.68 with 10 students who completed or 62.5%. Then in cycle II the class average score became 80.62 with 14 students or 87.5% of the total students who completed. The conclusion of this research is that the application of the direct instruction learning model can improve the understanding of the concept of the food chain in grade V SD Negeri 2 Muruh in the academic year 2020/2021